The Effect of Oxygen Partial Pressure during Active Layer Deposition on Bias Stability of a-InGaZnO TFTs*Supported by the National Basic Research Program of China under Grant Nos 2010CB327504, 2011CB922100 and 2011CB301900, the National Natural Science Foundation of China under Grant Nos 11104130 and 61322112, the Natural Science Foundation of Jiangsu Province under Grant Nos BK2011556 and BK2011050, and the Priority Academic Program Development of Jiangsu Higher Education Institutions, and the NUPTSF Grant Nos NY213069 and NY214028. (July 2015) - Huang, Xiao-Ming; Wu, Chen-Fei; Lu, Hai; Ren, Fang-Fang; Zhu, Hong-Bo; Wang, Yong-Jin
<x content-type="archive" xml:space="preserve">Abstract</x> The effect of oxygen partial pressure (PO2) during the channel layer deposition on bias stability of amorphous indium-gallium-zinc oxide (a-IGZO) thin film transistors (TFTs) is investigated. As PO2 increases from 10% to 30%, it is found that the device shows enhanced bias stress stability with significantly reduced threshold voltage drift under positive gate bias stress. Based on the x-ray photoelectron spectroscopy measurement, the concentration of oxygen vacancies (OV) within the a-IGZO layer is suppressed by increasing PO2. Meanwhile, the low-frequency noise analysis indicates that the average trap density near the channel/dielectric interface continuously drops with increasing PO2. Therefore, the improved interface quality with increasing PO2 during the channel layer deposition can be attributed to the reduction of interface OV-related defects, which agrees with the enhanced bias stress stability of the a-IGZO TFTs.